THE EFFECTS OF FINANCIAL RATIO, LOCAL SIZE AND LOCAL STATUS ON FINANCIAL DISTRESS - Novica Indriaty; Doddy Setiawan; Yuwita Ariessa Pravasanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This study is aimed to examine the effects of financial ratio empirically, local size and local status on financial distress. The status of financial distress is the condition of the inability of the local government to repay the loan principal and the loan interest. The population of this study include local governments in Indonesia that publish Report on Local Government Finances in 2008-2014. Samples were selected based on purposive sampling method and obtained 641 as research observation. With logistic regression, this study found that financial ratio included current ratio (CR), debt to equity ratio (D/E), operating revenues to total revenues ratio (OR/TR), return on assets ratio (ROA), return on equity ratio (ROE), and macro-economic variables were local size and local status have a significant effect on financial distress. Keywords : Financial Distress, Financial Ratio, Local Size, Local Status, Logistic Regression, Report on Local Government Finances